Methods of structural and dynamic analysis of commodity portfolio companies (Путеводитель предпринимателя, 2020)
This article describes the basic techniques used in portfolio analysis: а matrix analysis of the range, portfolio analysis, the matrix of Boston Consulting Group, McKinsey matrix, ABC-analysis.